Mengelola Penelitian Mini Mahasiswa Menjadi Penerbitan Prosiding - wahyudin darmalaksana; Busro Busro; Ali Rahman (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
Students often ask how to publish paper assignments. This study aims to discuss the management of mini-research into proceedings publishing. This research is a qualitative type through literature study and field studies by applying a content analysis approach. The results and discussion show opportunities to write mini-research papers according to standard guidelines, conduct presentation of papers at conference scientific forums, and publish a collection of papers in the form of proceedings. This study concludes that a collection of mini-research papers has the potential to become a proceeding publication if it is managed optimally by academics. This study recommends optimizing the management of student mini research papers for the opportunity to publish proceedings.